Sexual dimorphism of dermatoglyphic features in Type 2 diabetes mellitus patients of West Bengal: A cross-sectional study - Sarkar, Satabdi; Shahin Salma Khatun; Pallab Kumar Saha; Samanwita Basak; Bhaskar Pal; Arpita Sarkar (Asian Journal of Medical Sciences, 2024)
Background: Dermatoglyphics is the study of epidermal ridge patterns on the fingers, palms, and soles. Correlation of dermatoglyphic patterns with many chromosomal abnormalities and genetic predisposing diseases such as diabetes mellitus, hypertension, schizophrenia, and bronchial asthma is evidenced by many researchers. Literature on sexual dimorphism of dermatoglyphic patterns revealed it as an important characteristic feature. Aims and Objectives: The aim of the study is to study the variance of ridge patterns among male and female patients of Type 2 diabetes mellitus patients of West Bengal and determine the sex-specific digital and palmar ridge patterns in Type 2 Diabetes mellitus. Materials and Methods: A cross-sectional study has been done on 100 male and 100 female Type 2 diabetes mellitus patients. Digital and palmar prints were taken by the traditional ink method. Digital ridge pattern, pattern intensity index, total finger ridge count (TFRC), absolute finger ridge count (AFRC), and a-b ridge count were studied. The data on these patterns was recorded and statistically analyzed by Chi-square test and Student’s t-test. Results: The frequency of ulnar loop is higher in female diabetics in comparison to male diabetics. Statistically significant increase in mean TFRC and mean AFRC is seen in male diabetics. Conclusion: Our study exhibits that dermatoglyphic pattern significantly differs in male and female diabetics. The knowledge and reference range of dermatoglyphic parameters among male and female diabetics are essential in the use of this study as a screening tool or diagnostic tool in Type 2 diabetes mellitus.